Degenerate hope bifurcations in Chua's system - Messias, Marcelo [UNESP]; De Carvalho Braga, Denis; Mello, Luis Fernando (World Scientific Publishing, 2009)
In this paper we study the local codimension one, two and three Hopf bifurcations which occur in the classical Chua's differential equations with cubic nonlinearity. A detailed analytical description of the regions in the parameter space for which multiple small periodic solutions bifurcate from the equilibria of the system is obtained. As a consequence, a complete answer for the challenge proposed in [Moiola & Chua, 1999] is provided. © 2009 World Scientific Publishing Company.
Keywords: Chaotic attractor; Chua's equations; Degenerate Hopf bifurcation; Limit cycle; Lyapunov coefficient; Control nonlinearities; Hopf bifurcation